Long term mechanical performance of nano-engineered high volume fly ash concrete. (November 2021) - Herath, Charith; Gunasekara, Chamila; Law, David W.; Setunge, Sujeeva
Abstract: High Volume Fly Ash (HVFA) concrete is a sustainable construction material which can act as a viable alternative to Portland cement (PC) concrete. This study investigates the long-term mechanical performance of two unique HVFA concrete mixes, 65% and 80% cement replacements, incorporating hydrated lime, up to 18%, and 3% nano silica. HVFA-65 concrete achieved compressive strength values increasing from 32 to 73 MPa, from 7 to 450 day while HVFA-80 displayed a strength increase from 22 to 71 MPa in the same period. The flexural strength of HVFA-65 concrete increased from 3.6 to 8.7 MPa while the splitting tensile strength and elastic modulus gave values of 2.7–5.8 MPa and 30.3–40.5 GPa, respectively. Meanwhile, HVFA-80 concrete achieved flexural strengths of 2.7–8.7 MPa, splitting tensile strengths of 1.6–5.0 MPa and an elastic modulus of 28.9–37.0 GPa. Analysis of paste samples identified the presence of 11%, 3.2%, 5.3% and 2.1% higher concentrations of Portlandite within the HVFA-65 system at 7, 28, 90 and 450 days respectively, indicating a high availability of portlandite for the pozzolanic reaction of the fly ash. In microstructural investigation, HVFA-65 concrete displayed a denser gel matrix and stronger bond within the interfacial transition zone (ITZ) boundary compared to HVFA-80 at all ages. In addition, a statistical regression analysis conducted to predict relationships between long term mechanical properties of HVFA concrete are compared with existing design equations available in Australian Standards and ACI codes. Highlights: HVFA-65 and HVFA-80 concretes achieved 73 MPa of compressive strength at 450 days. HVFA concrete produces strongly compacted ITZ that illustrates to higher tensile strength. AS & ACI standards significantly underestimate the flexural strength of HVFA concrete. Splitting tensile strength & elastic modulus of HVFA concrete follow AS & ACI standards. Lime provides added CH for pozzolanic reaction of nano silica modified HVFA composite.